Bioactive Natural Products : Chemistry and Biology - Brahmachari, Goutam (Weinheim, Germany : Wiley-VCH, 2015)
Natural compounds, which have evolved their function over millions of years, are often more efficient than man-made compounds if a specific biological activity is needed, e.g. as an enzyme inhibitor or as a toxin to kill a cancer cell. This book comprising of sixteen technical chapters, highlights the chemical and biological aspects of potential natural products with an intention of unravelling their pharmaceutical applicability in modern drug discovery processes. Key features: Covers the synthesis, semi-synthesis and also biosynthesis of potentially bioactive natural productsFeatures chemi.
4.6 Fermentation and Nutritional Studies4.7 Other Activities of Immunosuppressants; 4.8 Concluding Remarks; Acknowledgments; References; Chapter 5 Activators and Inhibitors of ADAM-10 for Management of Cancer and Alzheimer's Disease; 5.1 Introduction to ADAM Family of Enzymes; 5.2 ADAM-10 Structure and Physiological Roles; 5.3 Pathological Significance; 5.3.1 Modulating ADAM Activity in Neurodegeneration; 5.3.2 ADAM-10 in Cancer Pathology; 5.4 ADAM-10 as Potential Drug Target; 5.5 Synthetic Inhibitors of ADAM-10; 5.6 Natural Products as Activators and Inhibitors for ADAM-10.
Includes bibliographical references and index.
Vendor-supplied metadata.
Keywords: Natural products; Biochemistry; SCIENCE / Chemistry / Organic; Biochemistry; Natural products; Electronic books; Electronic books